From Knowledge to Wisdom: The Educational Teachings Found in Quranic Verses - Saehudin Saehudin (Multidisciplinary: Journal of Education an Learning, 2025)
This article aims to explore the concept of education as outlined in the Quran, particularly focusing on how knowledge is transformed into wisdom. The study examines Quranic verses that emphasize the importance of knowledge, learning, and moral development, providing an insight into the role of education in shaping individuals and society. The research uses a library research approach, analyzing key Quranic verses that address education, knowledge, and wisdom. The literature review consists of classical and contemporary Islamic scholarship on educational principles derived from the Quran. The study reveals that Quranic verses do not only promote the acquisition of knowledge but also stress the importance of wisdom. The Quran links knowledge with moral integrity, spiritual growth, and practical application, shaping a balanced and holistic educational framework. This article provides insights for educators and policymakers in Islamic contexts, proposing that the Quranic teachings can help foster a deeper understanding of knowledge and its ethical application in modern education. It also highlights the need for a balanced educational approach that nurtures both intellectual and moral capacities